Multiwavelength observations of the unusual ultraluminous supernova SN 1978K in NGC 1313 and the search for an associated gamma-ray burst - Smith, I.; Ryder, S.; Tingay, Steven; Böttcher, M.; Liang, E.; Pakull, M.; Stacy, A. (2009)
We summarize our radio (Australia Telescope Compact Array and Australian Long Baseline Array) and X-ray (XMM-Newton) monitoring observations of the unusual ultraluminous supernova SN 1978K in the nearby (4.13 Mpc) latetype barred spiral galaxy NGC 1313 at ~ 25 - 30 years after the explosion. We also discuss the search for an associated gamma-ray burst. Full details and references are provided in Smith et al. (2007, ApJ, 669, 1130). © 2009 American Institute of Physics.